Detecting decadal scale increases in anthropogenic CO2 in the ocean. Issue 13 (2nd July 2014) - Kouketsu, Shinya; Murata, Akihiko M.
Abstract We used two methods to evaluate the uncertainty of estimates of decadal scale increases of anthropogenic CO2 in the ocean: analysis of changes along observation sections and analysis of gridded data produced by a statistical model. Both methods yielded similar results, although some differences were apparent. Clear differences existed where large estimation uncertainties were associated with the use of gridded data. The sparsity of observations and influences of isopycnal heaving, water mass shifts, and other factors accounted for the large uncertainties of the estimates. Our results clearly indicated that more frequent observations will be necessary to understand anthropogenic CO2 changes around Antarctica, which is an important anthropogenic CO2 sink. The rate of increase of global anthropogenic CO2 storage in the most recent decade was estimated to be 28.7 Pg C decade−1 on the basis of changes along sections, which is a little larger than previous estimates based on model studies. The uncertainty based on the statistical method was as much as ±4.4 Pg C decade−1.